Implementation of the MANDIRI-D innovation program for effective digital-based patient discharge planning in the hospital: Implementasi program inovasi MANDIRI-D untuk perencanaan pemulangan pasien berbasis digital yang efektif di rumah sakit - Ningsih, Sri Wahyuningsih; Karuniawaty, Sari Dewi Karuniawathy; Rondhianto, Rondhianto; Triandana, I Komang Leo Triandana (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2026)
Suboptimal discharge planning in hospitals remains a critical issue, contributing to high readmission rates and inadequate patient and family readiness for post-hospital care. This community service activity aimed to improve the effectiveness of discharge planning through the implementation of the MANDIRI-D innovation program, a digital-based approach utilizing QR Codes. The program provided accessible discharge information, including care guidelines, flowcharts, and patient education materials tailored to patient needs. The activity involved 20 patients and family members using a quasi-experimental pre–post design without a control group. Interventions included structured education delivered at least one day prior to discharge, access to QR Code-based educational media, and reinforcement through the teach-back method. The results demonstrated an improvement in patient knowledge and readiness for discharge (Δ total score 1.05), increased nurse compliance with discharge planning standard operating procedures (≥85%), and more efficient delivery of patient education. The MANDIRI-D program effectively enhanced patient and family preparedness, improved the quality of nursing services, and has the potential to reduce readmission rates. This innovation is recommended for broader implementation and integration into hospital electronic medical record systems to support sustainable and standardized discharge planning practices.